2022
DOI: 10.1155/2022/6339715
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Curcumin and Vitamin E on Inflammatory-Oxidative Stress Biomarkers and Primary Symptoms of Menopause in Healthy Postmenopausal Women: A Triple-Blind Randomized Controlled Trial

Abstract: Aims of the Study. Reducing estrogen levels due to menopause activates oxidative and inflammatory processes, which causes symptoms of menopause, anxiety, and sexual dysfunction. As a suggestion, potential anti-inflammatory and antioxidant agents such as curcumin and vitamin E could be used as an effective alternative treatment due to parsimony, suitable access, and fewer side effects. Therefore, the present study was conducted to find out whether supplementation with curcumin and vitamin E affects inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Curcumin causes a reduction in serum nitric oxide release in women with primary dysmenorrhea and premenstrual syndrome pain (Farrokhfall et al., 2023 ). It also decreases the total score of primary symptoms of menopause by affecting oxidative Stress Biomarkers (Farshbaf‐Khalili et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin causes a reduction in serum nitric oxide release in women with primary dysmenorrhea and premenstrual syndrome pain (Farrokhfall et al., 2023 ). It also decreases the total score of primary symptoms of menopause by affecting oxidative Stress Biomarkers (Farshbaf‐Khalili et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin causes a reduction in serum nitric oxide release in women with primary dysmenorrhea and premenstrual syndrome pain(Farrokhfall et al, 2023). It also decreases the total score of primary symptoms of menopause by affecting oxidative Stress Biomarkers(Farshbaf- Khalili et al, 2022).Bax, Bcl2l1 (Bcl-2), and Caspase 3 are crucial regulators in the apoptotic pathway, playing pivotal roles in determining cell fate.Specifically, Bax and Caspase 3 promote apoptosis, whereas Bcl2l1 counteracts these effects. The delicate balance among these factors serves as a key determinant in cellular survival and programmed cell death(Czabotar & Garcia-Saez, 2023).…”
mentioning
confidence: 99%
“…It was also found that in monkeys and rats undergoing ovariectomy, there was an increase in NKB gene expression. This process was reversed after estradiol therapy [ 14 , 31 , 32 , 33 ]. GnRH secretion is controlled by the functional neural network of the kisspeptin-neurokinin B-dynorphin (KNDy) arcuate nucleus system.…”
Section: The Kisspeptin-gnrh Pathwaymentioning
confidence: 99%
“…In the early years of menopause, curcumin supplementation may improve indicators of oxidative stress such as total antioxidant capacity (TAC), malondialdehyde (MDA), and biomarker of inflammation high-sensitivity C-reactive protein (hs-CRP) [ 31 ]. The exact molecular mechanism has not been determined, but, for example, the protective effects of curcumin in age-related cellular senescence are accomplished by inhibiting oxidative stress through upregulation of SIRT1 and NRF2 and downregulation of the p53/p21 pathway [ 57 ].…”
Section: Inflammatory and Oxidative Stress Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation